Modern Methods Of Conflict Resolution In Project Team Management - Alikulov Hazrat Amirkulovich (Genius Journals, 2024)
In the article, the opinions of the world's leading scientists on ways to resolve conflicts in the management of the project team in investment projects are studied, the hypothesized model of conflict detection in the management of the project team in investment projects is studied, the theories of human resources management are systematized, the cooperative method of conflict management is analyzed in this regard, the resolution of conflicts in the management of the project team in investment projects is studied. justified conclusions and suggestions on ways to do it have been developed.
Keywords: Investment project; project team; conflict types